Anodic Formation of Self-Organized Cobalt Oxide Nanoporous Layers - Lee, Chong-Yong; Lee, Kiyoung; Schmuki, Patrik (Angewandte Chemie International Edition, 2013)
High-aspect-ratio, ordered porous Co3O4 layers were formed by self-organizing anodization of a cobalt substrate and subsequent annealing. The key for successful formation of such layers is to sufficiently suppress competing oxygen evolution during anodization. The aligned Co3O4 channel layers behave as a highly efficient water oxidation catalyst.
EAM Import::2019-03-13

Anodic Nanotubular/porous Hematite Photoanode for Solar Water Splitting: Substantial Effect of Iron Substrate Purity - Lee, Chong-Yong; Wang, Lei; Kado, Yuya; Killian, Manuela; Schmuki, Patrik (ChemSusChem, 2014)
Anodization of iron substrates is one of the most simple and effective ways to fabricate nanotubular (and porous) structures that could be directly used as a photoanode for solar water splitting. Up to now, all studies in this field focused on achieving a better geometry of the hematite nanostructures for a higher efficiency. The present study, however, highlights that the purity of the iron substrate used for any anodic-hematite-formation approach is extremely important in view of the water-splitting performance. Herein, anodic self-organized oxide morphologies (nanotubular and nanoporous) are grown on different iron substrates under a range of anodization conditions, including elevated temperatures and anodization supported by ultrasonication. Substrate purity has not only a significant effect on oxide-layer growth rate and tube morphology, but also gives rise to a ninefold increase in the photoelectrochemical water-splitting performance (0.250 vs. 0.028mA cm-2 at 1.40V vs. reversible hydrogen electrode under AM1.5 100mW cm-2 illumination) for 99.99 % versus 99.5 % purity iron substrates of similar oxide geometry. Elemental analysis and model alloys show that particularly manganese impurities have a strong detrimental effect on the water-splitting performance.
EAM Import::2019-03-13

A significant cathodic shift in the onset potential of photoelectrochemical water splitting for hematite nanostructures grown from Fe-Si alloys - Wang, Lei; Lee, Chong-Yong; Kirchgeorg, Robin; Hildebrand, Helga; Müller, Julian; Spiecker, Erdmann; Schmuki, Patrik (Materials Horizons, 2014)
Thermal oxidation of Fe to nanostructured hematite (wires, flakes) is currently widely investigated to produce efficient photoanodes for photoelectrochemical water splitting. The process carried out on pure iron, however, has the key drawback that not only hematite but a layered structure of Fe2O3-Fe3O4-FeO is formed where the thick suboxide layer underneath the Fe2O3 is highly detrimental to the photoresponse. In the present work, we show that suboxide formation can be largely suppressed if hematite nanowires/nanoflakes are thermally grown on Fe-Si alloys. For hematite structures grown on a Fe-Si alloy with 5 at% Si, a photocurrent onset potential as low as 0.6 V-RHE can be reached (under AM 1.5 illumination and 1 M KOH). We believe that the results represent a key finding towards the formation of optimized hematite nanostructures using a thermal oxidation method.

Enhancing the Water Splitting Efficiency of Sn-Doped Hematite Nanoflakes by Flame Annealing - Wang, Lei; Lee, Chong-Yong; Mazare, Anca Valentina; Lee, Kiyoung; Müller, Julian; Spiecker, Erdmann; Schmuki, Patrik (Chemistry - A European Journal, 2014)
The effect of flame annealing on the water-splitting properties of Sn decorated hematite (-Fe2O3) nanoflakes has been investigated. It is shown that flame annealing can yield a considerable enhancement in the maximum photocurrent under AM 1.5 (100mWcm(-2)) conditions compared to classic furnace annealing treatments. Optimizing the annealing time (10s at 1000 degrees C) leads to a photocurrent of 1.1mAcm(-2) at 1.23V (vs. RHE) with a maximum value 1.6mAcm(-2) at 1.6V (vs. RHE) in 1M KOH. The improvement in photocurrent can be attributed to the fast direct heating that maintains the nanoscale morphology, leads to optimized Sn decoration, and minimizes detrimental substrate effects.
Keywords: doping; hematite nanoflakes; water splitting

Improved photoelectrochemical water splitting of hematite nanorods thermally grown on Fe–Ti alloys - Wang, Lei; Lee, Chong-Yong; Schmuki, Patrik (Electrochemistry Communications, 2014)
Here we show that hematite ( extgreeka-Fe2O3) nanostructures with a high water splitting performance can be formed on Fe–Ti alloys using the most simple thermal treatment in air and Ar. The use of the Fe–Ti alloy suppresses the formation of thick suboxide underlayers that are strongly detrimental for the photoconversion efficiency. The formed nanorod structures show an onset potential of up to 0.6–0.7 VRHE. This beneficial effect is attributed to the combination of suppression of a thick suboxide and the nature of the extgreeka-Fe2O3 nanorods after Ar annealing.
EAM Import::2019-03-13

Self-organized cobalt fluoride nanochannel layers used as a pseudocapacitor material - Lee, Chong-Yong; Su, Zixue; Lee, Kiyoung; Tsuchiya, Hiroaki; Schmuki, Patrik (Chemical Communications, 2014)
Aligned CoF2 nanochannel layers have been formed by self-ordering electrochemical anodization. In voltammograms these layers provide multiple oxidation states, an almost ideal rectangular pseudocapacitive behavior, a high specific capacitance and good capacitance retention. These layers may thus be promising for supercapacitor applications.
EAM Import::2019-03-13

Si-doped Fe2O3 nanotubular/nanoporous layers for enhanced photoelectrochemical water splitting - Lee, Chong-Yong; Wang, Lei; Kado, Yuya; Kirchgeorg, Robin; Schmuki, Patrik (Electrochemistry Communications, 2013)
The present work reports the enhancement of the photoelectrochemical water splitting performance of in-situ silicon (Si)-doped nanotubular/nanoporous (NT/NP) layers. These layers were grown by self-organizing anodization on Fe-Si alloys of various Si content. The incorporation of Si is found to retard the layer growth rates, leads to a more pronounced nanotubular morphology, and most importantly, an improved photoelectrochemical behavior. By increasing Si content from 1, 2 to 5 at.% in the iron oxide NT/NP photoanodes, the photocurrent onset potential shifts favorably to lower values. At 1.3 V vs. RHE, hematite layer with 5 at.% Si shows a 5-fold increase of the photocurrent, i.e. 0.5 mA cm- 2 in comparison to 0.1 mA cm- 2 for the undoped samples. The study also reveals that a suitable layer thickness is essential to achieve a beneficial effect of the Si doping.
EAM Import::2019-03-13

Solar water splitting: preserving the beneficial small feature size in porous α-Fe2O3 photoelectrodes during annealing - Wang, Lei; Lee, Chong-Yong; Schmuki, Patrik (Journal of Materials Chemistry A, 2012)
We prepared mesoporous extgreeka-Fe2O3/FTO electrodes by a simple anodic precipitation and annealing method. The classic problem is that when annealed in air at >500 °C, the individual particle size increases from ≈20 nm to 40–60 nm. This grain growth is highly detrimental for the water splitting efficiency. In the present work we show that grain coarsening can efficiently be prevented by a two-step annealing method in Ar, leading to photocurrent densities for such electrodes (obtained in 1 M KOH solution) of up to 2.6 mA cm-2 at 1.6 V vs. RHE under AM 1.5 100 mW cm-2 illumination, which is significantly higher than 1.5 mA cm-2 for conventionally annealed samples.
EAM Import::2019-03-13

Thermal air oxidation of Fe: rapid hematite nanowire growth and photoelectrochemical water splitting performance - Grigorescu, Sabina Georgiana; Lee, Chong-Yong; Lee, Kiyoung; Albu, Sergiu; Paramasivam, Indhumati; Demetrescu, Ioana; Schmuki, Patrik (Electrochemistry Communications, 2012)
Different iron oxide structures were formed by annealing of iron foils in air at temperatures between 500 °C to 800 °C. Depending on temperature, a significant variation in the hematite/magnetite ratio and a strongly temperature dependent morphology is obtained. While over a wide range of conditions more or less compact Fe3O4/Fe2O3 layers are obtained, at 600 °C rapid growth (several micrometer per hour) of highly crystalline hematite nanowires can be observed. Visible light photocurrent measurements in 1 M NaOH under AM 1.5 100 mW/cm2 conditions show that photocurrent density and the onset potential for water oxidation strongly shifted in the cathodic direction for the nanowire morphology. The results indicate that a simple air oxidation of iron can provide a rapid path to form hematite nanowires. Obtained layers are considerably active as photoanodes for solar water splitting.
EAM Import::2019-03-12